2014
DOI: 10.1371/journal.pone.0087936
|View full text |Cite
|
Sign up to set email alerts
|

The Heme Oxygenase System Suppresses Perirenal Visceral Adiposity, Abates Renal Inflammation and Ameliorates Diabetic Nephropathy in Zucker Diabetic Fatty Rats

Abstract: The growing incidence of chronic kidney disease remains a global health problem. Obesity is a major risk factor for type-2 diabetes and renal impairment. Perirenal adiposity, by virtue of its anatomical proximity to the kidneys may cause kidney disease through paracrine mechanisms that include increased production of inflammatory cytokines. Although heme-oxygenase (HO) is cytoprotective, its effects on perirenal adiposity and diabetic nephropathy in Zucker-diabetic fatty rats (ZDFs) remains largely unclear. Up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 84 publications
4
38
0
1
Order By: Relevance
“…Increasing evidence shows that MIP-1 α is overproduced and functionally activated to induce migration of T cells and macrophages to the kidney during diabetic and nondiabetic chronic kidney diseases [273, 274]. MIP-1 α is increased in urine of patients with crescentic glomerulonephritis, whereas its cognate receptors, CCR1 and CCR5, are expressed In CD3 ++ T cells and CD 68 + macrophages which infiltrate the glomeruli and interstitium.…”
Section: Progression Of Renal Injury Through Diverse Signaling Patmentioning
confidence: 99%
“…Increasing evidence shows that MIP-1 α is overproduced and functionally activated to induce migration of T cells and macrophages to the kidney during diabetic and nondiabetic chronic kidney diseases [273, 274]. MIP-1 α is increased in urine of patients with crescentic glomerulonephritis, whereas its cognate receptors, CCR1 and CCR5, are expressed In CD3 ++ T cells and CD 68 + macrophages which infiltrate the glomeruli and interstitium.…”
Section: Progression Of Renal Injury Through Diverse Signaling Patmentioning
confidence: 99%
“…Induction of HO-1 by several inducers such L-4F, CoPP, heme, or by gene transfer 4,113,114,172,174176 is associated with an increased number of healthy adipocytes, a concomitant increase of plasma adiponectin levels, improved insulin sensitivity and a decrease in inflammatory adipokines and blood pressure 20,24,115,172,174,175,177 . This effect of HO-1 induction on adipocyte morphology was confirmed in Zucker diabetic rats 175 and extended to ob/ob diabetic mice, where increased levels of HO-1 and HO activity prevented weight gain and decreased visceral and subcutaneous fat levels. Additional studies have reported that upregulation of HO-1 decreases adipogenesis in mesenchymal stem cells (MSCs) and increases adiponectin levels in culture media, which is reversed by the inhibition of HO activity 4,114 .…”
Section: Ho-1/ho-2 and Health Impactmentioning
confidence: 99%
“…1), which would greatly improve glucose metabolism, through enhanced adenosine monophosphate-activated protein kinasedependent glucose transporter 4 (GLUT4) expression and translocation (15). The antidiabetic effect observed with CoPP could be due to potentiation of insulin-sensitizing pathways (22) through HO upregulation similarly to increases in the activity of other factors which also promote insulin signaling such as adiponectin (22,(37)(38)(39)(40), cyclic guanosine monophosphate (cGMP), cyclic adenosine monophosphate (36), and peroxisome proliferatoractivated receptor α (36).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological activation of HO-1 may fall below the threshold necessary to activate important components through which the HO system can restore tissue homeostasis. Stronger effects can be achieved by some pharmacological agents capable of inducing some HO, like metalloprotoporphyrins such as cobalt protoporphyrin (CoPP) (39).…”
Section: Introductionmentioning
confidence: 99%